Cytotoxic effect induced by retinoic acid loaded into galactosyl-sphingosine containing liposomes on human hepatoma cell lines - Díaz Oreiro, Cecilia (2006)
Two retinoids, ATRA and 13cisRA, were incorporated into liposomes of different composition and charge and added to two hepatoma cell lines with different degree of transformation to measure cytotoxicity by MTT assay. Retinoid-free cationic liposomes were more toxic than the other kinds (anionic and made only of PC) but were also the best delivery system for retinoic acid to induce specific cytotoxic effects on these tumor hepatoma cell lines. Galactosyl-sphingosine containing cationic liposomes increased the cytotoxic effect induced by ATRA on Hep3B cells when compared to glucosyl-sphingosine cationic liposomes, but did not improve the effect induced by free retinoid or ATRA loaded into liposomes without glycolipids. This suggests that in this cell line, ATRA is being incorporated by a mechanism mediated by the asialoglycoprotein receptor, but at the same time, non-specific sugar-independent capture is also taking place as well as free diffusion of ATRA directly through the membrane. Galactose-specific effect was not observed in HepG2 cells treated with ATRA or both cell lines treated with 13cisRA. In fact, treatment of HepG2 cells with retinoids entrapped into liposomes likely induces proliferation instead of cytotoxicity, a result that interferes with the measurement of cell death by MTT. Compared to the specific effect of ATRA entrapped into cationic liposomes, vesicles made only by PC, did not mediate a specific mechanism, since differences between ATRA in galactosyl- and glucosyl-shpingosine PC-liposomes were not statistically significant. The specific mechanism was not present in the myoblastic cell line C2C12, where ATRA incorporated into galactosyl- and glucosyl-sphingosine containing cationic and PC-liposomes, was able to induce cytotoxicity at the same extent. Micelles containing ATRA and galactosyl-sphingosine had a significantly more toxic effect than the retinoid administered together with glucosyl-sphingosine, in Hep3B cells. Also, micelles containing ATRA were more toxic than glycolipid-containing liposomes with ATRA, for both kinds of sphingosines. The same effect was not observed in C2C12 cells, where glycolipid-containing liposomes worked better than micelles, and a sugar-specific mechanism was not seen. This suggests that, even though galactose-containing cationic liposomes could be a promising approach, a galactose-specific emulsion system could be the best strategy to specifically deliver retinoic acid to liver tumor cells, since it shows tissue specificity (perhaps induced by ASGPR-mediated internalization) and a stronger cytotoxic effect than the retinoid incorporated into liposomes.